Transitions to adulthood: self‐governance and disciplining in the making of patient citizens. Issue 3 (30th October 2019) - Renedo, Alicia; Miles, Sam; Marston, Cicely
Abstract: Young people develop new behaviours and redefine their identities during health transitions when they move from paediatric to adult healthcare environments. Their identities help to guide their health‐related actions in response to life changes. Young people's health is increasingly recognised as important, yet we lack understanding of how health transitions shape identities and how they relate to other transitions to adulthood. We conducted a longitudinal interview study with young people with sickle cell disease to explore how young people define new identities as they transition to adulthood. We show how 'disciplining at a distance' via healthcare self‐management discourses and neoliberal norms governing adolescence play out in the tensions participants encounter when they are crafting new identities. Health transitions involve struggles to negotiate competing demands for self‐discipline. It is crucial to create enabling spaces for young people to protect their health while still developing identities that help them achieve life goals.